O2C Laser Doppler and Digital Photo Analysis for Treatment Evaluation of Beta-Glucan versus Provitamin Pantothenic Acid of Facial Burns - Thieme, Daniel; Spilker, Gerald; Lefering, Rolf; Weinand, Christian (Facial Plastic Surgery, 2016)
Various creams are available for superficial second-degree burns (SSDB) of the face. We evaluated provitamin pantothenic acid versus β-glucan for SSDB of the face using the O2C laser Doppler system and digital photo analysis. Out of 20 patients (January to December 2012) with facial burns, 7 with SSDB of both cheeks were included to our study. Burned cheek wounds were treated using pantothenic acid or β-glucan. Digital photos of marked regions were taken daily from predefined distances. Microcirculation was measured at marked regions for 7 days at scheduled time points using the O2C laser Doppler. Data were evaluated using the SPSS program (SPSS Inc., Chicago, IL). Wounds treated with β-glucan showed faster reepithelialization. O2C laser Doppler measurements showed faster increase in SO2, microvascular perfusion, hemoglobin content, and blood flow. This correlated good with clinical Vancouver Scar Scale results. Although not statistically significant, β-glucan cream therapy of SSDB results in aesthetically superior outcome and faster reepithelialization.
Keywords: facial superficial second-degree burns; β-glucan; provitamin pantothenic acid; O2C laser Doppler; healing time; aesthetic results